The French Enlightenment in America Essays on the Times of the Founding Fathers - Valsania, Maurizio (Georgia Open History Library, 1984)
The French Enlightenment in America offers an overview of French American cultural relations during the French Enlightenment. The essays in this volume explore the literary presence of French authors in America between 1760 and 1800 and the reception of their writings by the Founding Fathers and other Americans. These essays explore such topics as the Founding Fathers' knowledge of French, the philosophes, Voltaire in the South, and more. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.